(untitled) (Delta Medical College Journal, 2025)
Background: Plateletpheresis is a process in which healthy donor blood is passed through an apparatus that separates platelets, returning the remaining components to circulation. Objective: To determine the frequency of adverse donor reactions during plateletpheresis procedure. Materials and method: This retrospective study was carried out in Department of Transfusion Medicine of BIRDEM General Hospital at Dhaka, Bangladesh,from January 2020 to December 2021. A total of 275 healthy male blood donors participated after providing informed written consent and were selected according to the national guideline’s Standard Operating Procedure (SOP). Data on adverse effects experienced by donors during the plateletpheresis procedure were recorded and analyzed retrospectively. Results: Among the participants, 12(4.36%) donors encountered various reactions. Specifically, 7(2.54%) donors had mild hypocalcemic symptoms, 3(1.09%) donors developed local reactions like hematoma and swelling at the venipuncture site and 2(0.73%) donors reported mild vasovagal reactions. Among those affected 8 (66.6%) donors were undergoing plateletpheresis for the first time, while 4(33.4%) donors were repeat donors. Conclusion: Effective training for technical personnel and supervision by transfusion specialists are crucial for minimizing donor reactions during apheresis procedures. Close monitoring and timely interventions improve the donor experience, ensuring safety and comfort throughout the procedure. Delta Med Col J. Jul 2022;10(2): 39-44